Hanseniella sp (Symphyla) nova praga rizófaga de Ananas comosus (L) Merr, no Brasil - Camargos Loureiro, Milgar; Maurício Fortes , José (Revista Ceres, 2025)
For the first time in Brazil, in 1970, Hanseniella sp. (Symphyla, Scutigerellidae) was reported as a root pest of the pineapple crop (dnanas comosus L. Merr.). Due to the attack of this arthropod, 37% of one planting in Viçosa, State of Minas Gerais, presented the following symptoms; (a) deficiency in growth; (b) smaller number of leaves, some of which showed a reddish yellow tone and whose distal extremities had a tendency to dry out; and (c) a smaller leaf area. The fruits, when present, were approximately 1/2 the size of those of normal plants, with a drastically reduced root system. An experiment was initiated to determine the severity of the root pest and the corresponding symptoms. Six months after the begining of the experiment there began a gradual decline in the aerial parts of the control plants, which by the end of the experiment resembled in appearance the infested plants. In both, the symptoms were similar to those described above. It was verified that from the infested plants there was migration of Hanseniella sp. to the controls, masking the desired resuts.